2018
DOI: 10.1111/ibi.12577
|View full text |Cite
|
Sign up to set email alerts
|

Sex identification in King Penguins Aptenodytes patagonicus through morphological and acoustic cues

Abstract: In the context of sexual selection, animals have developed a variety of cues conveying information about the sex of an individual to conspecifics. In many colonial seabird species, where females and males are monomorphic and do not show obvious differences in external morphology, acoustic cues are an important signal for individual and sex recognition. Here, we study the vocal and morphological sex dimorphism in the King Penguin Aptenodytes patagonicus, a colonial, monomorphic seabird for which our knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 81 publications
0
18
1
Order By: Relevance
“…the resonant frequencies (Titze 1994, Taylor andReby 2010). Although this theory is valid in mammals, the relationships between frequencies and body size remains unclear in birds (Galeotti et al 1997, Mager et al 2007, Favaro et al 2017, Kriesell et al 2018 but see Patel et al 2010).…”
Section: Relationship Between Acoustic Parameters and Morphological Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…the resonant frequencies (Titze 1994, Taylor andReby 2010). Although this theory is valid in mammals, the relationships between frequencies and body size remains unclear in birds (Galeotti et al 1997, Mager et al 2007, Favaro et al 2017, Kriesell et al 2018 but see Patel et al 2010).…”
Section: Relationship Between Acoustic Parameters and Morphological Traitsmentioning
confidence: 99%
“…A well-known example is the fundamental frequency (or pitch) which negatively correlates with body size (e.g. Galeotti et al 1997, Mager et al 2007, Favaro et al 2017, Kriesell et al 2018. In many species, larger males have a higher breeding success because body mass is an indicator of physical strength and/or foraging success (Chastel et al 1995, Salton et al 2015 and females rely on fundamental frequency as a sexual signal (review in Cardoso 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Species such as Adélie (Pygoscelis adeliae), king (Aptenodytes patagonicus) and gentoo penguins (P. papua) use their calls to facilitate mate and chick identification as parents or partners return to the noisy colonies. Individuality can be conveyed through certain parameters including call duration, amplitude modulation rates, spectrum bandwidth and distribution of energy among harmonics (Humphries et al, 2016;Jouventin et al, 1999;Kriesell et al, 2018;Ligout et al, 2016;Mathevon, 1997). In Wilson's storm-petrels (Oceanites oceanicus) and several auk species, chicks in poorer condition emit higher frequency calls, and these higher pitched calls also result in the chick receiving increased care, including larger meals (Gladbach et al, 2009;Klenova, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The display calls of king penguins Aptenodytes patagonicus have been shown to be emitted during mate choice [39] and sex-differences in the fundamental frequency of the calls and the syllable pattern have been identified [40]. Furthermore, playback experiments have shown that the king penguin call is vital for individual recognition [41,42].…”
Section: Introductionmentioning
confidence: 99%